Heavy metal contamination of soil based on pollution, geo-accumulation indices and enrichment factor in Phan Me coal mine area, Thai Nguyen province, Vietnam - Hoang, Nguyen Van; Dao, Le Quang; Van, Dong Thu; Hoa, Pham Lan (Vietnam Journal of Earth Sciences, 2020)
Soil samples around the Phan Me coal mine area, Thai Nguyen province, Vietnam had been analyzed for Fe, Mn, Cu, Zn, As, Cd, Hg, Pb and Ni. Single pollution index, geo-accumulation index, enrichment factor have been determined and used for assessing the soil quality. In average by pollution index, the soil heavy metal pollution sequence is Cu(PI=4.2)>Cd(3.5)>Zn(3.1) >Pb(1.7)>Ni(1.3). High concentrations of Cu, Zn and Cd in the soil in the study area are thanks to geo-accumulation and enrichment of the metals in the soil. The soil is from moderately to heavily contaminated by Cu, Zn and Cd: Cu and Zn concentrations are 1.5-2.8 times higher than the ecological risk values, and Cd concentration is about 3.5 times higher than allowable limits. The high concentration of Pb is thanks to moderate geo-accumulation and enrichment of Pb, and the soil mostly has Pb concentration higher than the allowable limit in about 1.7 times. There is a sign that the soil is contaminated by Ni: 22% of the samples have Ni concentration higher than the threshold value, however, the enrichment of Ni is only deficient to minimal. The results of the assessment highlight the need for a comprehensive and detailed study program on heavy metal content in different soil resources in a wider area to identify the magnitude and details of the problem associated with heavy metal contamination for the development of a remediation plan and more effective pollution preventing measures.